2022
DOI: 10.3390/computers11020023
|View full text |Cite
|
Sign up to set email alerts
|

A Project-Scheduling and Resource Management Heuristic Algorithm in the Construction of Combined Cycle Power Plant Projects

Abstract: Given the growing number of development projects, proper project planning and management are crucial. The purpose of this paper is to introduce a heuristic algorithm for scheduling a power plant project construction and project resource management to determine the size of project buffers and feeding buffers. This algorithm consists of three steps: 1. estimating the duration of project activities; 2. determining the size of the project buffer and feeding buffers; and 3. simulating the mentioned algorithm, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Determine the duration of activities, 2. demonstrating the size of the project buffer and feeding buffers, And 3. a simulation of the proposed algorithm. The findings demonstrated that the appropriate number of buffers can be assigned for projects using the proposed algorithm [8]. In another research, Zohrehvandi et al proposed a project buffer and resource management (PBRM) algorithm to optimize project resources and the size of the project buffer, and control of consumption of the project buffer in a renewable project to achieve a more realistic project duration and project completion time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Determine the duration of activities, 2. demonstrating the size of the project buffer and feeding buffers, And 3. a simulation of the proposed algorithm. The findings demonstrated that the appropriate number of buffers can be assigned for projects using the proposed algorithm [8]. In another research, Zohrehvandi et al proposed a project buffer and resource management (PBRM) algorithm to optimize project resources and the size of the project buffer, and control of consumption of the project buffer in a renewable project to achieve a more realistic project duration and project completion time.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The idea of adding a time margin to the minimal project completion time as a time buffer and using it in case of delayed occurrences was introduced by Zohrehvandi et al [35]. Other research conducted by Zohrehvandi et al in the field of modeling and optimization in scheduling and project buffer management could refer to these cases [36][37][38][39].…”
Section: Literature Reviewmentioning
confidence: 99%